Research on the Letter to the Galatians: 2000-2020. Volume 2 Research on the Letter arranged according to Pericopes - Tolmie, Donald Francois (UJ Press, 2023)
This book confirms that research on the Letter to the Galatians is flourishing. Although it is true that much of what is being published is not new and that well-known arguments and insights have often been repeated, it is also clear that much progress is constantly being made. In this volume, hundreds of academic studies that appeared on the letter from 2000 to 2020 are discussed concisely so that the main contribution of each study to one's understanding of the letter can be grasped easily. The letter is divided into eighteen pericopes and the studies that appeared on a specific pericope are classified in terms of five categories - introductory matters, textual and stylistic issues, history of interpretation, interpretative approaches and the theology of the pericope. The primary focus of each study is clearly delineated so that its specific contribution to grasping key aspects of the pericope becomes clear. D. Francois Tolmie is Professor of New Testament Studies at the Faculty of Theology and Religion at the University of the Free State, Bloemfontein, South Africa. He is also the author of Persuading the Galatians: A Text-Centred Rhetorical Analysis of a Pauline Letter and Pointing Out Persuasion in Philemon: Fifty Readings of Paul's Rhetoric from the Fourth to the Eighteenth Century.